2000
DOI: 10.2307/2641098
|View full text |Cite
|
Sign up to set email alerts
|

Louisiana Estuarine and Coastal Fisheries and Habitats: Perspectives from a Fish's Eye View

Abstract: Stimulated by nutrients from the Mississippi River, the vast coastal wetlands of the river's past and present deltas interface with the Gulf of Mexico to form a complex and prolific marine ecosystem. This highly productive system has yielded annual fishery landings of Ͼ453.6 ϫ 10 6 kg (1 billion pounds) since 1969. The Louisiana ecosystem has been heavily exploited and significantly altered over the years to meet the demands for coastal development, seafood production, navigation, oil exploration, flood contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…Prior studies suggested that as adult fish in open systems can migrate away from areas affected by hypoxia (Craig et al, 2001) impacts will most likely be confined to health effects, behavioral alterations and changes in habitat selection (Chesney and Baltz, 2001). Additionally, efforts to link changes in fish production to hypoxia are often obscured by fishing effects (Chesney et al, 2000). Nonetheless, even in open systems, serious, long-term impacts such as altered distribution, changes in trophic interactions and mortality of early life-history stages are predicted (Breitburg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggested that as adult fish in open systems can migrate away from areas affected by hypoxia (Craig et al, 2001) impacts will most likely be confined to health effects, behavioral alterations and changes in habitat selection (Chesney and Baltz, 2001). Additionally, efforts to link changes in fish production to hypoxia are often obscured by fishing effects (Chesney et al, 2000). Nonetheless, even in open systems, serious, long-term impacts such as altered distribution, changes in trophic interactions and mortality of early life-history stages are predicted (Breitburg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although hypoxia occurs naturally in systems characterized by low light and low mixing (e.g. heavily vegetated wetlands), the frequency of hypoxia is increasing globally through the influx of municipal waste and fertilizers that accelerate eutrophication (Chesney et al 2000;Pollock et al 2007). It has thus become increasingly important to understand the consequences of low-oxygen stress on fish populations.…”
Section: Discussionmentioning
confidence: 99%
“…3), little or no overlap occurs between 'normoxic' and 'hypoxic' sites within region (Figs 2 and 3). Moreover, waters with dissolved oxygen that drops below 2.8 mg/L (Diaz & Rosenberg 1995;Wu 2002) or 2.0 mg/L (Chesney et al 2000) have been considered hypoxic in previous studies. While the oxygen at the Manywa, Juma, and Dead Duck Bay sites often rose above these values (Fig.…”
Section: Samplingmentioning
confidence: 99%
“…The inputs of anthropogenically derived nitrogen (N) to the oceans may now exceed inputs from natural sources (Howarth et al 1996;Vitousek et al 1997), and much of these loads pass through estuaries. Estuaries mediate the N flux between nitrogen-rich watersheds and nitrogen-limited coastal oceans and have been suggested as important sites for nutrient attenuation, cycling, and support of secondary production (Nixon et al 1996;Chesney et al 2000;Eyre 2000). Despite the importance of this link between fluvial and marine environments, there is currently an incomplete understanding of the mechanisms of N transformations, storage, and export within estuaries.…”
mentioning
confidence: 99%